Membangun inovasi organisasi antara kepemimpinan transformasional dan kompetensi kepemimpinan di situasi pandemi pada grandmas airport - I Gusti Putu Ngurah Yuliwana Putra; Putri Anggreni; I Made Arjana (STIMI Handayani Denpasar, 2023)
This study took the object of tourism employees at Grandmas Airport. The findings are that it is difficult for companies to innovate when hotel operations are running in a COVID-19 pandemic. The leadership factor (leadership style) is a type of leadership that needs to be improved, which affects leadership competence is the education factor that has not been evenly distributed so that it hinders organizational innovation considering that there are still many fresh graduates. The purpose of this study was to determine the effect of transformational leadership and leadership competence in building organizational innovation in the COVID-19 pandemic situation. 19 at Grandmas Plus Hotel Airport. This study uses a quantitative method with a total population of all hotel employees with a sample of 35 employees determined by the saturated sampling method or census. Sources of research data from monthly reports and data collection techniques by observation, interviews and distributing questionnaires. For technical analysis using multiple linear regression in accordance with the steps of Sugiyono, 2015: 348 with SPSS windows version 25 application tools. Meanwhile for instrument testing using validity and reliability tests, as well as hypothesis testing using f test and t test. The results of this study are the transformational leadership variable has a positive relationship on organizational innovation, the leadership competence variable has a positive relationship on organizational innovation and the transformational leadership variable and leadership competence have a simultaneous effect on organizational innovation with a significant value.